Power Loss Research on IGCT-applied NPC Three-level Converter - Dong Xu; MinXiao Han; Lei Wan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
IGCT has a broad application prospects in high power conversion such as flexible DC transmission due to its characteristics of high voltage and large capacity. Compared with IGBT it has a voltage and current level of 4.5kV/4kA and its slope resistance is less than IGBT’s. In addition, due to the di/dt snubber circuit, IGCT’s opening loss will be reduced. Because of improvement of IGCT performance, the loss of IGCT-applied three-level converter will have some new characteristics, so it is necessary to model the IGCT-type three-level converter. Based on piecewise linear curve fitting method, the IGCT switching loss mathematical model is established firstly. With its use in IGCT-type three-level converter loss model, a IGCT-type three-level converter mathematical model is established. If the model is applied in the ±200kV flexible DC transmission’s calculation example, it can be concluded that the loss rate is 0.31%-0.78% when the power factor angle changes between 0 and π, while the loss rate of IGBT-type converter under same voltage level is 2%-3.5% ,so it can be concluded that IGCT is more suitable than IGBT for use in high voltage and large capacity situation such as frequency control of motor speed and flexible DC transmission.